Blood Pressure and Living Kidney Donors: A Clinical Perspective. Issue 10 (October 2019) - Rastogi, Anjay; Yuan, Stanley; Arman, Farid; Simon, Lewis; Shaffer, Kelly; Kamgar, Mohammad; Nobakht, Niloofar; Bromberg, Jonathan S.; Weir, Matthew R.
Abstract : Elevated blood pressure (BP), or "hypertension, " has been one of the main exclusion criteria for living kidney donation, as it is a risk factor for renal and cardiovascular disease. The effect of elevated BP in living kidney donors is not well studied or understood. The most current living kidney donation guidelines state that donors with a BP >140/90 mm Hg with 1–2 antihypertensive medications or evidence of end-organ damage should be excluded from living kidney donation. Yet, the definitions of "hypertension" have changed with the release of the American Heart Association (AHA)/American College of Cardiology (ACC) clinical practice guidelines suggesting that 120–129 mm Hg is elevated BP and Stage 1 hypertension is 130 mm Hg. However, the kidney function (in terms of estimated GFR) of "hypertensive" living kidney donors does not fare significantly worse postdonation compared with that of "normotensive" donors. In addition, even though living kidney donation itself is not considered to be a risk factor for developing hypertension, there exist certain risk factors (African American or Hispanic descent, obesity, age) that may increase the risk of living kidney donors developing elevated BP postdonation. The choice of BP targets and medications needs to be carefully individualized. In general, a BP <130/80 mm Hg is needed, along with lifestyle modifications.